Clinical Profile of Bacterial Meningitis in Children and Comparative Inter-Alia Analysis of Various Microbiological Tests - Halder, Rohan; Malik, Richa; Aggarwal, K.C; Nair, Deepthi; Sharma, Shobha (Journal of Child Science, 2020)
Acute bacterial meningitis (ABM) is a life-threatening and neurologically debilitating infectious disease. We studied the clinical profile, organisms involved in bacterial meningitis in children, and compared the tests on cerebrospinal fluid (CSF), latex agglutination test (LAT), polymerase chain reaction (PCR), Gram stain (conventional) and Cyto-Tek cytospin centrifuge Gram stain to culture which is the gold standard. This was an observational cross-sectional study (age range 3 to 12 months) conducted in a tertiary care hospital, New Delhi, India over 1 year. A total of 101 patients were enrolled and divided into three age groups, namely, < 1 year, 1 to 5 years, and > 5 years. Fever was the most common presenting symptom in all groups (84.2%). Refusal to feed, headache, altered sensorium, vomiting, and blurring of vision were significantly associated with bacterial meningitis in all age groups. Cranial nerve palsies and neck rigidity were significantly higher in older children. Age < 5years, low-socioeconomic status, overcrowding, and smoke exposure were identified as risk factors for meningitis. Eight children died within 48 hours of admission and the rest (n = 93) recovered without complications. CSF culture was positive in 35.6% cases, with streptococcus pneumoniae being the most common organism. PCR was most sensitive (86.1%) and cytospin gram stain showed positivity in 65% cases which was statistically higher compared with conventional gram stain. Cytospin-prepared Gram stain was a viable low-cost alternative for early diagnosis of meningitis in low-income countries like India.
Keywords: clinical features; culture; PCR; cytospin-prepared Gram stain